2019
DOI: 10.1039/c9dt01905g
|View full text |Cite
|
Sign up to set email alerts
|

Non-mutagenic Ru(ii) complexes: cytotoxicity, topoisomerase IB inhibition, DNA and HSA binding

Abstract: Herein we discuss five ruthenium(ii) complexes with good cytotoxicity against cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…[ 19 ] The increased K b value for RuBDQ at 308 K indicated that this complex could be transported and stored in the body using HSA. As previously published, the K b values for systems based in metallodrugs and HSA are in the range 10 4 to 10 6 M −1 , [ 13,45–48 ] and the optimum K b value varied with the type of drug and therefore the path that interacted with HSA. [ 49 ]…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…[ 19 ] The increased K b value for RuBDQ at 308 K indicated that this complex could be transported and stored in the body using HSA. As previously published, the K b values for systems based in metallodrugs and HSA are in the range 10 4 to 10 6 M −1 , [ 13,45–48 ] and the optimum K b value varied with the type of drug and therefore the path that interacted with HSA. [ 49 ]…”
Section: Resultsmentioning
confidence: 85%
“…The magnitude of the HSA‐binding constant (K b ) for RuBDQ and RuBD, compared with other Ru(II) compounds previously reported, suggested that they produced a moderate interaction with the HSA molecule. [ 48 ]…”
Section: Resultsmentioning
confidence: 99%
“…The activity of coordination cationic compounds (most relevant depicted in Scheme 5) in TNBC are linked to a variety of cellular mechanisms such as DNA interactions and apoptotic cell death, among others. [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112] Ratanaphan and co-workers focused on elucidating cellular effects on BRCA1-defective cells with compound 32 ([Ru(Clazpy) 2 phen]Cl 2 • 8H 2 O in Scheme 5), a Ru(II) coordinated complex with the bidentate ligand 5-chloro-2-(phenylazo)pyridine. [94] Cytotoxicity was observed in MDA-MB-231 (IC 50 = 13.2 � 0.3 μM, 24 h) and BRCA1-defective HCC-1937 (IC 50 = 1.8 � 0.1 μM, 24 h) cell lines, along with cell cycle inhibition at G2/M phase and an apoptotic mechanism of cell death.…”
Section: Ruthenium (Ii) Compoundsmentioning
confidence: 99%
“…[98] The enhancement of anticancer activity through possible synergistic effects by using bioactive ligands has also been explored with ruthenium coordination compounds (all depicted in Scheme 6). The Batista group has developed a number of these complexes, [99][100][101][102][103][104] which include the incorporation of ligands with known anticancer activity such as lapachol (compound 37) [99] and cinnamic acid (compound 38). [103] These Ru complexes have shown enhanced cytotoxic activity in MDA-MB-231 cells (37 IC 50 = 0.20 � 0.01 μM, 38 IC 50 = 1.9 � 0.05 μM, 48 h) and have shown anti-invasion and anti-migration properties and interactions with HSA in initial mechanistic studies.…”
Section: Ruthenium (Ii) Compoundsmentioning
confidence: 99%
“…Moreover, Bhat et al [26] recently reported trisheteroleptic Ru-complexes that exhibit the "molecular light switch" effect and are toxic against HeLa and HL-60 cell lines, while cellular uptake is localized in the cell nucleus. ese reports show the high potential of Rutrisheteroleptic complexes in the design of multimodal metallotherapeutic agents [27].…”
Section: Introductionmentioning
confidence: 99%